1984
DOI: 10.1111/j.1600-0404.1984.tb07807.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous progesterone infusions on the epileptic discharge frequency in women with partial epilepsy

Abstract: Earlier work showed that in a group of women suffering from partial epilepsy, there is a decrease in seizure frequency during the luteal phase of the menstrual cycle. Moreover, iv progesterone infusions decrease the discharge frequency from penicillin epileptic foci in cats, when given in doses that reach plasma concentrations as observed during pregnancy. In the present study, iv progesterone infusions, reaching plasma concentrations as during the luteal phase, were given to 7 women with partial epilepsy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0
6

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(87 citation statements)
references
References 10 publications
(6 reference statements)
4
76
0
6
Order By: Relevance
“…The results of the present work confirm the importance of sex steroids in the modulation of central nervous system excitability and seizure threshold, a fact which may have clinical relevance, since increased incidence of seizures has been reported in susceptible women during declining progesterone levels across the menstrual cycle (Backstrom et al 1984;Schachter 1988;Herzog 1995). Progesterone has also been suggested as a helpful therapy in treating seizures (Zimmerman 1986), and testosterone combined with an aromatase inhibitor has been used to improve sexual function and reduce seizures in men with epilepsy (Herzog 1999b).…”
Section: Discussionsupporting
confidence: 86%
“…The results of the present work confirm the importance of sex steroids in the modulation of central nervous system excitability and seizure threshold, a fact which may have clinical relevance, since increased incidence of seizures has been reported in susceptible women during declining progesterone levels across the menstrual cycle (Backstrom et al 1984;Schachter 1988;Herzog 1995). Progesterone has also been suggested as a helpful therapy in treating seizures (Zimmerman 1986), and testosterone combined with an aromatase inhibitor has been used to improve sexual function and reduce seizures in men with epilepsy (Herzog 1999b).…”
Section: Discussionsupporting
confidence: 86%
“…Protection against epileptic seizures was one of the first identified central actions of exogenously administered progesterone (Selye, 1942;Craig, 1966), and it is believed that fluctuations in endogenous progesterone levels can affect seizure susceptibility in women with epilepsy (Bä cktröm et al, 1984;Herzog, 1999;Rogawski and Reddy, 2004). In recent years, numerous studies have confirmed the powerful anticonvulsant activity of progesterone in diverse animal seizure models (Landgren et al, 1978;Holmes and Weber, 1984;Reddy and Kulkarni, 1997;Mohammad et al, 1998;Kokate et al, 1999;Frye and Scalise, 2000).…”
mentioning
confidence: 99%
“…Progesterone metabolites such as allopregnanolone, in contrast, are potent barbiturate-like ligands at the GABA-chloride ionophore (1 1). Progesterone reduces neuronal metabolism (12) and discharge rates (13), and suppresses kindling (14), epileptiform discharges (15), and experimental (16) as well as clinical seizures (17).…”
mentioning
confidence: 99%